Norma dan Penyelesaian Sengketa di Pengadilan Pajak Berdasarkan Azas Kepastian Hukum: Kasus Sengketa Gugatan - HARYONO, HARYONO; Subagyo, Sugeng; Jutawan, M. Donduan; Sufiarina, Sufiarina (Jurnal Hukum Positum, 2025)
One of the aims or ideals of law is the aspect of legal certainty, in addition to the elements of justice and legal utility. This study aims to analyse the regulatory norms concerning the submission and resolution of lawsuits at the Tax Court from the perspective of legal certainty, particularly in terms of the time frame. The researcher conducted the study using a normative juridical method based on the Law on the Tax Court, examining the regulatory norms for filing and resolving lawsuits, as well as conducting an empirical legal review of the lawsuits. The results of the study show that in the pre-hearing stage, the regulatory norms for lawsuits are clearly established. However, during the trial examination stage up to the pronouncement of the judgment, there is no clear regulation concerning time provisions, especially regarding the time frame for delivering the judgment as stipulated in Article 81 of the Tax Court Law. The implementation of the pre-hearing stage complies with the provisions of Article 81 of the Tax Court Law, whereas in the trial examination stage up to the pronouncement of the judgment, several decisions exceeded the time limit as provided for in Article 81 of the Tax Court Law.